DAMPAK LOCKDOWN COVID 19 PADA PENDIDIKAN ISLAM DI INDONESIA - Nurullita Almunawaroh (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
Muslim communities have very high expectations in the success and progress of Islamic education. However, that hope has not been fully implemented until now, because there are still many problems in the world of Islamic education as we face now the impact of holding a lockdown from a virus that struck the national and international level namely covid-19, as a result it does not only have an impact on the economy of the community Indonesia is bad, It also has a positive and negative influence on the world of Islamic education in Indonesia. The purpose of this research is to find a way to prioritize comfort, readiness, safety, and public health. Of course, these steps are taken as part of the covid-19 pandemic response system. The research method use is qualitative based on quality in the form of research data sources obtained for educational research data and the covid-19 of outbreak data and the data related to this research in scientific journalism. This research also a systematic procedure approach. the results of this study indicate that educators and students in Islamic education throughout the world, especially throughout Indonesia, velg The tremendous impact of the covid-19 virus outbreak, Which In addition to this outbreak, Which In addition to the outbreak had an impact on the learning process of education in Islamic schools, but the impact of it is implementation this lockdown provides wisdom to the state of Indonesia that can make some people aware and feel the development of technology and educational learning application features that have advanced very rapidly, with this society will be more familiar with technology specifically in learning Islamic education.